Influence of prenatal transportation stress-induced differential DNA methylation on the physiological control of behavior and stress response in suckling Brahman bull calves - Littlejohn, Brittni P (J Anim Sci, 2019)
The objective of this experiment was to examine potential differential methylation of DNA as a mechanism for altered behavioral and stress responses in prenatally stressed (PNS) compared with nonprenatally stressed (Control) young bull calves. Mature Brahman cows (n = 48) were transported for 2-h periods at 60 ± 5, 80 ± 5, 100 ± 5, 120 ± 5, and 140 ± 5 d of gestation (Transported group) or maintained as nontransported Controls (n = 48). From the offspring born to Transported and Control cows, a subset of 28-d-old intact bulls (n = 7 PNS; n = 7 Control) were evaluated for methylation of DNA of behavior and stress response–associated genes. Methylation of DNA from white blood cells was assessed via reduced representation bisulfite sequencing methods. Because increased methylation of DNA within gene promoter regions has been associated with decreased transcriptional activity of the corresponding gene, differentially methylated (P ≤ 0.05) CG sites (cytosine followed by a guanine nucleotide) located within promoter regions (n = 1,205) were used to predict (using Ingenuity Pathway Analysis software) alterations to canonical pathways in PNS compared with Control bull calves. Among differentially methylated genes (P ≤ 0.05) related to behavior and the stress response were OPRK1, OPRM1, PENK, POMC, NR3C2, TH, DRD1, DRD5, COMT, HTR6, HTR5A, GABRA4, GABRQ, and GAD2. Among altered (P < 0.05) signaling pathways related to behavior and the stress response were Opioid Signaling, Corticotropin-Releasing Hormone Signaling, Dopamine Receptor Signaling, Dopamine-DARPP32 Feedback in cAMP Signaling, Serotonin Receptor Signaling, and GABA Receptor Signaling. Alterations to behavior and stress response–related genes and canonical pathways supported previously observed elevations in temperament score and serum cortisol through weaning in the larger population of PNS calves from which bulls in this study were derived. Differential methylation of DNA and predicted alterations to behavior and stress response–related pathways in PNS compared with Control bull calves suggest epigenetic programming of behavior and the stress response in utero.